A paraszti önellátás összgazdasági szerepéről - Csanády, András (Szociológiai Szemle, 2024)
In the Third World the urban unemployment is a reflexion of the rural one - say their experts. We try to interprete the present East-Central-European unemployment according of this pattern, and made our investigations in a little region of Transylvania on family-farms. There we found:- families are working in a very broad dividing of labour with relatives and neighbours;- they produce dominantly for own needs, and sell only few surpluses;- their taking urban/industrial employments plays only a supplementary role in supporting the family and its farming.